2015
DOI: 10.1093/pasj/psv072
|View full text |Cite
|
Sign up to set email alerts
|

Survey of period variations of superhumps in SU UMa-type dwarf novae. VII. The seventh year (2014–2015)

Abstract: Continuing the project described by Kato et al. (2009, PASJ, 61, S395), we collected times of superhump maxima for 102 SU UMa-type dwarf novae, observed mainly during the 2014-2015 season, and characterized these objects. Our project has greatly improved the statistics of the distribution of orbital periods, which is a good approximation of the distribution of cataclysmic variables at the terminal evolutionary stage, and has confirmed the presence of a period minimum at a period of 0.053 d and a period spike j… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 164 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…A positive superhump has previously been reported in Z Cha by Kato et al (2015) during a 2014 superoutburst of the source. They calculated the mean period of the superhump as 0.07736(8) d during the dominant evolutionary Stage B (see Kato et al 2009).…”
Section: Superhumpmentioning
confidence: 58%
See 3 more Smart Citations
“…A positive superhump has previously been reported in Z Cha by Kato et al (2015) during a 2014 superoutburst of the source. They calculated the mean period of the superhump as 0.07736(8) d during the dominant evolutionary Stage B (see Kato et al 2009).…”
Section: Superhumpmentioning
confidence: 58%
“…QZ Vir and IRXS J0532, Kato et al 2009), but the physical parameters which determine whether Stage A superhumps will occur in a given superoutburst remain unclear. Notably, a previous superoutburst of Z Cha in 2014 did show Stage A superhumps (Kato et al 2015), indicating that the absence of Type A superhumps is a property related to individual superoutbursts rather than to the system. Additionally, using our estimate of the superhump period at its onset, it is possible to obtain an independent estimate for the mass ratio q of the components of the Z Cha system, where q is the mass ratio defined as:…”
Section: Superhump Period and Evolutionmentioning
confidence: 98%
See 2 more Smart Citations
“…While this is roughly in agreement with the accretion rates estimated from observations (Townsley & Gänsicke 2009;Pala et al 2017), the theoretical framework outlined above fails to re-produce a number of observational properties of the Galactic population of CVs: (i) the predicted fractions of CVs above and below the period gap ( 1 per cent and 99 per cent, respectively, de Kool 1992; Kolb 1993;Howell et al 2001) are in clear disagreement with the observations (e.g. 23 per cent and 77 per cent, Gänsicke et al 2009, though the observed samples are typically magnitude-limited, and hence biased towards more luminous CVs); (ii) period bouncers are expected to be the main component ( 40 − 70 per cent) of the present-day Galactic CV population but only a small number of such systems has been identified (Patterson et al 2005;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al 2015Kato et al , 2016McAllister et al 2017;Neustroev et al 2017;Pala et al 2018); (iii) there are clues of the presence of additional AML mechanisms that are not accounted for by the standard model of CV evolution (Patterson 1998; Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017;Belloni et al 2018;Liu & Li 2019), although the physical origin of this enhanced AML is still unclear.…”
mentioning
confidence: 88%